2019
DOI: 10.1080/17415993.2019.1620230
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective chlorination of phenols in the presence of tetrahydrothiopyran derivatives

Abstract: Four six-membered cyclic sulfides, namely tetrahydrothiopyran, 3methyltetrahydrothiopyran, 4-methyltetrahydrothiopyran and 4,4dimethyltetrahyrdrothiopyran have been used as moderators in chlorination reactions of various phenols with sulfuryl chloride in the presence of aluminum or ferric chloride. On chlorination of phenol, ortho-cresol and meta-cresol the para/ortho chlorination ratios and yields of the para-chloro isomers are higher than when no cyclic sulfide is used for all of the cyclic sulfides, but chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Use of the cyclic dialkyl sulphides tetrahydrothiopyran and some methyl-substituted tetrahydrothiopyrans (6-9; Figure 3) produced similar results to dibutyl sulphide in reactions with phenol and m-cresol, and we showed that smaller quantities of both the dialkyl sulphide (0.28 mmol for 50 mmol of 1) and aluminium chloride (25-50 mg for 50 mmol of 1) could be used to gain similar levels of selectivity [63]. Under similar reaction conditions, the chlorination of o-cresol (1; R = 2-Me), which has only one ortho-position available for chlorination, was very selective towards the para-isomer 3 (R = 2-Me) with all of the tetrahydrothiopyrans 6-9, with the highest selectivity being achieved over unsubstituted tetrahydrothiopyran 6 (96% yield; para/ortho ratio = 45.7) [63]. Additional difficulties arise with m-xylenol, which melts at a higher temperature, thereby requiring a solvent for re-actions at the modest temperatures used for the other phenols, and where there is a limit with respect to the concentration of aluminium for the commercially important product, 4-chloro-m-xylenol.…”
Section: Results With Simple Dialkyl Sulphides and Some Cyclic Analoguessupporting
confidence: 54%
See 1 more Smart Citation
“…Use of the cyclic dialkyl sulphides tetrahydrothiopyran and some methyl-substituted tetrahydrothiopyrans (6-9; Figure 3) produced similar results to dibutyl sulphide in reactions with phenol and m-cresol, and we showed that smaller quantities of both the dialkyl sulphide (0.28 mmol for 50 mmol of 1) and aluminium chloride (25-50 mg for 50 mmol of 1) could be used to gain similar levels of selectivity [63]. Under similar reaction conditions, the chlorination of o-cresol (1; R = 2-Me), which has only one ortho-position available for chlorination, was very selective towards the para-isomer 3 (R = 2-Me) with all of the tetrahydrothiopyrans 6-9, with the highest selectivity being achieved over unsubstituted tetrahydrothiopyran 6 (96% yield; para/ortho ratio = 45.7) [63]. Additional difficulties arise with m-xylenol, which melts at a higher temperature, thereby requiring a solvent for re-actions at the modest temperatures used for the other phenols, and where there is a limit with respect to the concentration of aluminium for the commercially important product, 4-chloro-m-xylenol.…”
Section: Results With Simple Dialkyl Sulphides and Some Cyclic Analoguessupporting
confidence: 54%
“…Therefore, reactions were conducted in the presence of FeCl 3 (25 mg) in tetrachloroethylene (25 mL). Tetrahydrothiopyran 6 again provided the highest yield of 3 (R = 3,5-di-Me; 89.1%) with a para/ortho ratio of 13.5 on chlorination of m-xylenol (1; R = 3,5-di-Me) under these conditions [63]. We also tested some other simple sulphur compounds, such as sulphoxides and sulphones, as potential catalysts [62], but did not find any that were as good as the simple sulphides, especially dibutyl sulphide, di-iso-propyl sulphide, and tetrahydrothiopyran.…”
Section: Results With Simple Dialkyl Sulphides and Some Cyclic Analoguesmentioning
confidence: 88%
“…Chlorination of P using SO2Cl2 in the presence of the cyclic disulfide 1,2-dithiocane and AlCl3 at 25°C gave 2-CP (7.4%), 4-CP (91.2%), and 2,4-DCP (1.1%) [33], while use of the polymeric equivalent, poly(hexamethylenedisulfide), under similar conditions gave 2-CP, 4-CP and 2,4-DCP in 8.8, 89.0, and 2.2% yields, respectively [33]. The use of tetrahydrothiopyran as catalyst in chlorination of P using SO2Cl2 in the presence of AlCl3 at 25°C gave 2-CP and 4-CP in 5.0 and 89.0% yields, respectively [34], while chlorination of P using SO2Cl2 in the presence of 5,18-dithiadocosane and AlCl3 at 35°C gave 2-CP and 4-CP in 6.6 and 76.4% yields, respectively, along with unreacted starting material (11.4%) [35,36]. Methylthio alcohols, methoxy(methylthio)alkanes, and bis(methythio)alkanes have also been investigated as catalysts in chlorination of P using SO2Cl2 in the presence of AlCl3 at 25°C and led to the production 2-CP (8.2-12.7%) and 4-CP (83.1-88.8%) along with 2,4-DCP (1.6-2.3%) [37].…”
Section: Introductionmentioning
confidence: 91%
“…20 Current methods that halogenate one constitutional isomer rely on substrate modifications such as blocking the position of unwanted halogenation, or require the use of harsh conditions. 21,22 These methodologies cannot be applied for the use in late-stage functionalization (LSF) of pharmaceutically relevant scaffolds as they can irreversibly alter the substrate structure or are not functional group tolerant. 23 There is an unmet need to develop a method that relies on catalyst control to overcome a substrate's innate regioselectivity.…”
Section: The Regioselective Chlorination Of Phenolsmentioning
confidence: 99%